Single-switch, wide voltage-gain range, boost DC-DC converter for fuel cell vehicles - Zhang, Yun; Zhou, Lei; Sumner, M.; Wang, Ping (Institute of Electrical and Electronics Engineers, 2018)
In order to match voltages between the fuel cell stacks and the DC link bus of fuel cell vehicles, a single-switch Boost DC-DC converter with diode-capacitor modules is proposed in this paper. The capacitors are charged in parallel and discharged in series. The wide voltage-gain range can be obtained by using a simple structure. In addition, the basic operating principles, the extended stages, the fault tolerant operation, and steady-state characteristics of the converter are analyzed and presented in this paper, and the small-signal model is also derived. A 400V, 1.6kW experimental prototype is developed, and the wide voltage-gain range (3.3~8) is demonstrated with a maximum efficiency at 97.25%. The experimental results validate the effectiveness and feasibility of the proposed converter and its suitability as a power interface for fuel cell vehicles.